2015
DOI: 10.5603/fhc.a2015.0004
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and obestatin in thyroid gland — immunohistochemical expression in nodular goiter, papillary and medullary cancer

Abstract: Introduction. Previous studies analyzing ghrelin and obestatin expression in thyroid gland tissue are not unanimous and are mostly related to ghrelin. The role of ghrelin and obestatin in the thyroid gland appears very interesting due to their probable involvement in cell proliferation. Furthermore, since the thyroid gland is associated with the maintenance of energy balance, the relationship between ghrelin, obestatin and thyroid function is worthy of consideration. The aim of the study was to assess ghrelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…According to the obtained data, it may be assumed that FNDC5 gene expression in thyroid tissue is not associated with the development of thyroid malignancy. Such overexpression has been reported for several anti‐apoptotic proteins, such as nicotinamide phosphoribosyltransferase gene ( NAMPT ), ghrelin or BIRC5 encoding surviving …”
Section: Discussionmentioning
confidence: 89%
“…According to the obtained data, it may be assumed that FNDC5 gene expression in thyroid tissue is not associated with the development of thyroid malignancy. Such overexpression has been reported for several anti‐apoptotic proteins, such as nicotinamide phosphoribosyltransferase gene ( NAMPT ), ghrelin or BIRC5 encoding surviving …”
Section: Discussionmentioning
confidence: 89%
“…CSTPTCs may also be very aggressive, as demonstrated by the recurrence of the disease. Environmental, genetic, immunological, and hormonal factors are considered possible pathomechanisms for thyroid malignancy recurrence [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experimental and clinical studies demonstrated that ghrelin decreased blood pressure in healthy individuals and animals with normal blood pressure as well as animals with hypertension [13]. It was suggested that the mechanisms responsible for the hypotensive effects of ghrelin include the suppression of sympathetic activity or direct vasodilatory activities [5,14].…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa in other parts of the stomach and intestines contains distinctly lower ghrelin concentrations with the lowest being observed in the colon [3]. Another area participating in ghrelin synthesis is the central nervous system with the neurons of the arcuate nucleus in the hypothalamus being the most active [4] as well as thyroid gland [5].…”
Section: Introductionmentioning
confidence: 99%